Src Plays an Important Role in AGE-Induced Endothelial Cell Proliferation, Migration, and Tubulogenesis - Li, Peixin; Chen, Deshu; Cui, Yun; Zhang, Weijin; Weng, Jie; Yu, Lei; Chen, Lixian; Chen, Zhenfeng; Su, Haiying; Yu, Shengxiang; Wu, Jie; Huang, Qiaobing; et al. (Frontiers in Physiology, 2018)
Advanced glycation end products (AGEs), produced by the non-enzymatic glycation of proteins and lipids under hyperglycemia or oxidative stress conditions, has been implicated to be pivotal in the development of diabetic vascular complications, including diabetic retinopathy. We previously demonstrated that Src kinase plays a causative role in AGE-induced hyper-permeability and barrier dysfunction in human umbilical vein endothelial cells (HUVECs). While the increase of vascular permeability is the early event of angiogenesis, the effect of Src in AGE-induced angiogenesis and the mechanism has not been completely revealed. Here, we investigated the impact of Src on AGE-induced HUVECs proliferation, migration, and tubulogenesis. Inhibition of Src with inhibitor PP2 or siRNA decreased the AGE-induced migration and tubulogenesis of HUVECs. The inactivation of Src with pcDNA3/flag-SrcK298M also restrained AGE-induced HUVECs proliferation, migration, and tube formation, while the activation of Src with pcDNA3/flag-SrcY530F enhanced HUVECs angiogenesis alone and exacerbated the AGE-induced angiogenesis. The AGE-enhanced HUVECs angiogenesis in vitro was accompanied with the phosphorylation of ERK in HUVECs. The inhibition of ERK with its inhibitor PD98059 decreased AGE-induced HUVECs angiogenesis. Furthermore, the inhibition and silencing of Src suppressed the AGE-induced ERK activation. And the silencing of AGEs receptor (RAGE) inhibited the AGE-induced ERK activation and angiogenesis as well. In conclusions, it’s demonstrated that Src plays a pivotal role in AGE-promoted HUVECs angiogenesis by ERK phosphorylation, and very likely through a RAGE/Src/ERK pathway.